Numerical modelling of subduction zones : thermo-mechanical stabilization as a function of overriding plate rheology and thickness - Bolrão, Francisco José da Paz (2022)
Tese de Mestrado, Ciências Geofísicas (Geofísica Interna), 2022, Universidade de Lisboa, Faculdade de Ciências